Fullerenes generated from porous structures - Paupitz, Ricardo [UNESP]; Junkermeier, Chad E.; van Duin, Adri C. T.; Branicio, Paulo S. (Royal Soc Chemistry, 2014)
A class of macromolecules based on the architecture of the well-known fullerenes is theoretically investigated. The building blocks used to geometrically construct these molecules are the two dimensional structures: porous graphene and biphenylene-carbon. Density functional-based tight binding methods as well as reactive molecular dynamics methods are applied to study the electronic and structural properties of these molecules. Our calculations predict that these structures can be stable up to temperatures of 2500 K. The atomization energies of carbon structures are predicted to be in the range of 0.45 eV per atom to 12.11 eV per atom (values relative to the C60 fullerene), while the hexagonal boron nitride analogues have atomization energies between -0.17 eV per atom and 12.01 eV per atom (compared to the B12N12 fullerene). Due to their high porosity, these structures may be good candidates for gas storage and/or molecular encapsulation.